ISOLATION AND DISTRIBUTION OF CRUDE OIL AND POLYCYCLIC AROMATIC HYDROCARBON-DEGRADING BACTERIA FROM POLLUTED HARBOURS IN NORTH JAKARTA - Alfiansah, Yustian Rovi; Adindasari, Mindi; Argarini, Mentari; Darmayati, Yeti; Ruyitno, - (Marine Research in Indonesia, 2014)
Several harbours in North Jakarta have been polluted by spills of oil and their derivates. We suggest that diverse species of crude oil and polycyclic aromatic hydrocarbon-degrading bacteria Â inhabit these harbours. An experiment was undertaken in 2007 to isolate crude oil and polycyclic aromatic hydrocarbon (PAH)-degrading bacteria from oil-polluted harbours, such as Muara Baru, Sunda Kelapa and Tanjung Priok. Sea water and sediment samples were collected twice, in March and April. Crude oil and PAH-degrading bacteria were isolated from enrichment culture of samples in an enrichment medium (SWP), using ONR7a medium with the addition of 5 types of PAH gases or Arabian Light Crude Oil 210 (ALCO 210) onto medium. This study reported that fluoranthene and crude oil-degrading bacteria were the major bacteria isolated from the three polluted harbours. In total, 109 isolates have been collected which can degrade crude oil (29% of total isolates), fluoranthene (33%), fluorene (20%), pyrene (7%), dibenzothiopene (6%), and phenantrene (5 %). Among these isolates, 5 isolates have the capability to degrade 5 types of PAH and ALCO 210. They were Alcanivorax sp. B-1084, Pseudomonas sp. D5-38b, Alcanivorax sp. TE-9, Bacillus sp. L41, Alcanivorax dieselolei strain B-5 clone 1. Culturable bacteria have been isolated mostly from the Sunda Kelapa samples, with fewer in those from Muara Baru and Tanjung Priok, respectively